Nançay Decameter Array (NDA) Routine Sun Observation Data Collection - Lamy, Laurent; Le Gall, Alexandre; Cecconi, Baptiste; Loh, Alan; Renaud, Patrice; Masson, Sophie; Denis, Laurent; Coffre, Andrée; Zarka, Philippe; Lecacheux, Alain (PADC/CDN, 2021)
Decametric radio observation from Nançay Decameter Array (NDA). The NDA at the Station de Radioastronomie de Nancay (SRN) is a phased array of 144 "Teepee" helicoidal antenna, half of which being Right Handed (RH) polarized and the other half being Left Handed (LH) polarized. Four receivers are currently connected to the NDA, sampling data in spectral ranges within 5 to 80 MHz. This collection contains the Solar observation data products, in raw and CDF formats.
Keywords: Radio astronomy; The Sun